Pengaruh Budaya Oragnisasi, Motivasi Intrinsik, Motivasi Ekstrinsik Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada UPTD Puskesmas Rawat Inap Kotagajah - Kurniyanti, Rizka Minda; Suwarto, Suwarto; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2023)
Companies definitely need competent and qualified employees, especially in this era ofglobalization. All business organizations are the driving force in decisions to achieveorganizational goals. Organizational development is determined by the work of HR in theorganization. This study aims to determine 1) To find out whether organizational culture has aneffect on employee performance. 2) To find out whether Extrinsic Motivation has an effect onemployee performance. 3) To find out whether Intrinsic Motivation has an effect on employeeperformance. 4) To find out whether job satisfaction has an effect on employee performance. 5)To find out whether organizational culture, extrinsic motivation, intrinsic motivation, and jobsatisfaction together affect employee performance. This study uses a quantitative approach. Thesurvey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solveproblems. In this study, the population of this study were employees and some students who wereintern at the UPTD Inpatient Health Center Kotagajah were 84 people. The results showed that1) there was a positive and significant influence between organizational culture on employeeperformance. 2) there is a positive and significant influence between Extrinsic Motivation onemployee performance. 3) there is a positive and significant influence between intrinsicmotivation on employee performance 3) there is a positive and significant influence between jobsatisfaction on employee performance 4) there is a positive and significant influence betweenorganizational culture, extrinsic motivation, intrinsic motivation, and job satisfaction onperformance employee.